The Psychology of Christian Nationalism - Cooper-White, Pamela (Journal of pastoral theology, 2023)
This paper was presented at the Society for Pastoral Theology annual study conference, Montgomery, AL, June 10, 2022. It is based on the author's book The Psychology of Christian Nationalism: Why People Are Drawn In and How to Talk Across the Divide (Fortress Press, 2022). Cooper-White defines Christian nationalism as a social and political movement with the goal of restoring the US to a fictional origin as a ‘Christian nation’ with a not-at-all fictional origin in white, masculinist supremacy. Christian nationalism is a fanatical, radical departure from the teachings of Jesus and any faithful reading of the Hebrew Bible or the New Testament, and it is also dangerously anti-democratic. The paper offers an overview of current sociological research on Christian nationalism and its adherents; a discussion of conscious and unconscious motivations that draw people into extremist beliefs, including individual and group psychodynamics and the role of narcissistic demogogues (citing Freud); and how and under what circumstances to talk with people across this current extreme divide in American religion and politics without resorting either to disrespectful dialogue or to superficial appeals to unity.